The Influence of the Project Based Learning (PjBL) Learning Model in Civics Subjects on the Development of Students' Civic Skills at SMP Muhammadiyah 19 Pematangsiantar TP. 2022/2023 - Nisa, Khairun; Amin, Zulkifli (Holistic Science, 2023)
This research aims to find out the influence of the Project Based Learning (PjBL) learning model in Civics subjects on the development of student’s civic skills. This research uses quantitative research. The objects of this research were class VIII students of SMP Muhammadiyah 19 Pematangsiantar and data collection techniques used questionnaires, observation and documentation. The data analysis techniques used are validity tests, reliability tests, normality tests, and using the "t" test. Based on the calculation of the validity test there are 20 questions, after carrying out the validity test it is > 0.388 then it is declared that the whole is valid, the reliability test value (x) obtained is 0.640 and the value (y) obtained is 0.841 so it is declared reliable, the normality test value obtained is 0.197 then it is normally distributed. And after carrying out the "t" Paired Sample Test using SPSS 26.0, namely a sig value of 0.00, then sig < 0.05 (0.00 < 0.05). So, Ha is accepted, Ho is rejected. This proves that Civics learning on the development of student’s civic skills using the Project Based Learning (PjBL) learning model has an influence compared to before using the Project Based Learning (PjBL) learning model